DEVELOPMENT OF ELECTRONIC BOOKS BASED ON MULTIPLE REPRESENTATIONS ON MATTER PHYSICS - Lisa Apriyani; I Dewa Putu Nyeneng; Nengah Maharta (Jurnal Pembelajaran Fisika, 2013)
Based on the results of interview done by researchers against the junior high school in Bandar Lampung, is known that many students do not have learning resources such as books for use outside of school hours. It is known that the stu-dent's reason do not have a source of learning is the limited cost and the difficulty in getting it. Taking into account these problems, the researcher developed an electronic books as a learning resource. Electronic books are developed based on multiple representations to matter physics junior high school class VIII. The pur-pose of this development is to make the students more interested in learning and can develop students' understanding of physics concepts. Development's model used in this study was adapted from the model of media development and learn-ing according Suyanto and Sartinem (2009). Development's model includes five procedures product development and product testing, namely: preliminary re-search, creation of script/ design materials, product development, product testing (internal testing and external testing), and the dissemination and implementa-tion. Internal test results indicate that the learning resource has been developed in accordance with the content standards and fit for use as a learning resource for students. External test results showed that the quality of learning resource are very attractive, reaching 96% for attractive level of product and effective used as a learning resource, reaching 82% of students are complete the KKM. So, we can conclude that generated the learning resource such as electronic books based multiple representations that have been tested and fit for use with very attractive qualities and declared effective as a learning resource.Key words : development, electronic books and multiple representations.